Chapter 2 Family not to be informed? The ethical use of historical medical documentation - Meyer, Jessica (Social Histories of Medicine, 2021)
What are the ethics that shape or should shape engagement with historical medical data, particularly archives containing patient voices? This question has come to the fore through the 'Men, Women and Care' project, a European Research Council-funded project creating a database of information drawn from the PIN 26 personal pension award records from the First World War. Held by the National Archives, London, these records contain a wealth of personal information, including potentially sensitive details of medical conditions and diagnoses, as well as material concerning stigmatising social situations, such as domestic violence, prostitution and illegitimacy. Using material drawn from 'Men, Women and Care', this chapter considers the opportunities presented and challenges posed by this material as sources for historical analysis. It considers issues of both disciplinary practice and theoretical framing to explore the position of the historian in relation to analysing and disseminating the historical patient voice. In doing so, it asks what use historians can and should make of this information and what steps the historical community might consider taking to articulate a code of ethics around practice that is sensitive both to family feeling and academic enquiry.